DEVELOPMENTAL DISCUSSION AS AN EFFORT TO IMPROVE THE CRITICALTHINKING OF THE XI GRADE STUDENTS OF SMA NEGERI 5 YOGYAKARTATHROUGH THE SOCIOLOGY SUBJECT - Edy Purwanto; Asep Sumiaji; Heni Setiana (Pelita - Jurnal Penelitian Mahasiswa UNY, 2013)
The objective of the research was to improve the students’ critical thinking andthe quality of the learning process in the classroom by using the developmental discussionlearning model.This study was conducted in three cycles consisting of preparation, action,observation and reflection. The research data were collected through direct observation,tests and questionnaires.The results showed a significant activity of the students in a discussion in eachcycle. The evaluation results demonstrated the success of individual and group programscharacterized by an increase in the quality of the process and achievementreflected in the test scores.